Analysis of Electrical Properties of Fe3O4/Graphene Oxide Nanocomposites Synthesized from Corn Cob Waste - Febri Zola, Nadira; Hidayat, Rahmat; Gusnedi, Gusnedi; Jhora, Fadhila (Universitas Negeri Padang, 2024)
In this era of globalization, the needs of society continue to increase along with technological advances. The more sophisticated the technology, the higher the demand for electricity and energy storage. The energy storage medium that is widely used today is lithium batteries. But because the price of lithium batteries is quite high, the solution to overcome the high price of lithium batteries is to replace lithium battery electrodes with carbon-based materials such as Graphene Oxide. Graphene Oxide can be made from biomass waste, one of which is corn cob waste